Pengaruh Keselamatan dan Kesehatan Kerja (K3) terhadap Produktivitas Kerja Karyawan pada Pt. PLN (Persero) UP3 Bima - M. Arfan Akbar; Ikbal Irawan; Muhammad Yusuf (Institut Nalanda, 2024)
This research aims to determine the effect of occupational safety and health on work productivity. The sampling technique used in this research uses purposive sampling so that the sample used in this research is permanent employees at PT. PLN (PERSERO) UP3 Bima, totaling 56 people. Data collection techniques using observation, questionnaires and literature study. Data analysis technique using simple linear regression. The research results show that there is a significant influence between occupational safety and health on employee work productivity at PT. PLN (PERSERO) UP3 Bima.